PENYUSUNAN LAPORAN KEUANGAN BUMDES BERKAH MULIA BUKIT MULIA BERDASARKAN KEPMENDESA PDTT NO 136 TAHUN 2022 - Agustina, Imelda; Rininda, Bella Puspita; Ulfida, Deafatunnizwa; Rizka, Nor Rahma; Rahman, Gusti Yuni (Worksheet : Jurnal Akuntansi, 2025)
This research is conducted to develop financial statements for BUMDes Berkah Mulia Bukit Mulia in alignment with the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration Number 136 of 2022. The financial reports compiled include the balance sheet, income report, statement of equity changes, and notes to financial statements (CaLK). Using a descriptive qualitative approach, the data collection was carried out through observation, interviews, document analysis, and literature review. The results indicate that the BUMDes faced various obstacles in preparing financial reports, such as limited accounting knowledge among staff, ineffective use of government-provided applications, and reliance on basic spreadsheet tools for recording. Despite these challenges, the study succeeded in producing comprehensive financial statements for the December 2024 period that comply with Kepmendesa PDTT guidelines. These outcomes are anticipated to improve financial transparency and accountability while serving as a useful model for future reporting practices.